Offshore oil and gas in Russia: the legal framework and the implications as at September 1995 - Vidal, Tillman (Research of GSB, 2025)
The oil and gas industry in Russia is experiencing serious problems in the wake of the disintegration of the Soviet Union and the old structures with no new structures there to replace them. This applies to the whole of the Russian economy, and the way into a market economy with its regimes and structures is a very slow one in view of the political difficulties subsisting, with a general lack of understanding of the workings of a free market economy and democracy. While the free market economy is what is aspired, the use of the word 'free' in this context is often taken by its literal meaning in Russia. The oil and gas industry which is an important employer and above all foreign currency earner, is in the forefront of development. It is impossible to separate onshore and offshore oil and gas, in that there was a total lack of legislation in the Soviet Union on the oil and gas industry in general. Laws which were introduced were essentially territorial laws attempting to lay down rules and regulations. It is however noteworthy that it is precisely the large offshore projects which have been negotiated for a number of years already or are being negotiated at present, which seem to be a major factor behind the increasing legislative activity in the oil and gas industry, as these are without exception subject to a legal regime for the industry which is acceptable to investors seeking stability rather than a pure maximisation of profits. The attempts in introducing the production sharing legislation are a direct result of these projects as well as proposed legislation on the continental shelf.